Aleksandŭr Stamboliĭski Bulgaria - Crampton, R. J. (Haus histories, 2010)
Aleksandur Stamboliiski was one of the most original politicians of the 20th century. His tragedy was that he came to power at the end of the First World War in which Bulgaria had been defeated. It fell to him, therefore, to accept and apply the peace settlement. This created tensions between him and traditional Bulgarian nationalism, tensions which ended with his murder in 1923. The book will examine the origins of this traditional nationalism from the foundation of the Bulgarian state in 1878, and of the agrarian movement which came to represent the social aspirations of the majority of the peasant population. It will also illustrate Stamboliiski's rise to power and examine his ideology. Emphasis will be placed on how this ideology clashed with the monarchy, the military, and the nationalists. Stamboliiski's policies in the Balkan wars and the First World War will be described before the details of the 1919 peace settlement are examined. The implementation of those terms will then be discussed as will the coup of 1923. The legacy of the peace treaty in the inter-war period and of Stamboliiski's image in the years after his downfall will form the final section of the book.